Namco: a microbiome explorer. Issue 8 (2nd August 2022) - Dietrich, Alexander; Matchado, Monica Steffi; Zwiebel, Maximilian; Ölke, Benjamin; Lauber, Michael; Lagkouvardos, Ilias; Baumbach, Jan; Haller, Dirk; Brandl, Beate; Skurk, Thomas; Hauner, Hans; Reitmeier, Sandra; et al.
Abstract : 16S rRNA gene profiling is currently the most widely used technique in microbiome research and allows the study of microbial diversity, taxonomic profiling, phylogenetics, functional and network analysis. While a plethora of tools have been developed for the analysis of 16S rRNA gene data, only a few platforms offer a user-friendly interface and none comprehensively covers the whole analysis pipeline from raw data processing down to complex analysis. We introduce Namco, an R shiny application that offers a streamlined interface and serves as a one-stop solution for microbiome analysis. We demonstrate Namco's capabilities by studying the association between a rich fibre diet and the gut microbiota composition. Namco helped to prove the hypothesis that butyrate-producing bacteria are prompted by fibre-enriched intervention. Namco provides a broad range of features from raw data processing and basic statistics down to machine learning and network analysis, thus covering complex data analysis tasks that are not comprehensively covered elsewhere. Namco is freely available at https://exbio.wzw.tum.de/namco/ .